2016
DOI: 10.5152/eurasianjmed.2015.61
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Turkish "Basic Life Support" and "Cardiac Massage" Videos Uploaded to Websites

Abstract: Objective: In this study, the reliability of Turkish cardiac massage and Basic Life Support (BLS) videos, which have already been downloaded from three website such as YouTube, Google, Yahoo following the publication of 2010 cardiopulmonary resuscitation (CPR) guideline and their suitability to the same guideline were researched. Materials and Methods:The videos uploaded to the three website to search videos on internet were queried by using the keywords "cardiac massage" and "basic life support". Videos that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
3
3
0
5
Order By: Relevance
“…The average total score of the videos uploaded by official medical organizations (6.43 ± 3.57) was significantly higher than that of videos uploaded by unidentified sources (4.24 ± 2.39), consistent with previous reports [4, 9, 11]. With regard to information related to topics that directly affect human life, such as CPR, materials published by institutions that are constantly working in this field are more reliable.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The average total score of the videos uploaded by official medical organizations (6.43 ± 3.57) was significantly higher than that of videos uploaded by unidentified sources (4.24 ± 2.39), consistent with previous reports [4, 9, 11]. With regard to information related to topics that directly affect human life, such as CPR, materials published by institutions that are constantly working in this field are more reliable.…”
Section: Discussionsupporting
confidence: 87%
“…About 88% of the videos assessed in this study were excluded because they did not meet the inclusion criteria. Similarly, several previous studies examining the reliability of YouTube videos reported exclusion of 80%–94% of videos [4, 9, 11, 13]. As in these previous studies, we found that the high exclusion rate made it difficult to find the required content on YouTube.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Exclusion rate was previously found to be between 80% and 94% in various studies (9,11,16,17). The fact that the majority of the search results were excluded from the study indicates that most videos are uploaded with tags unrelated to the video content.…”
Section: Discussionmentioning
confidence: 97%
“…Bir çalışmada da kardiyak arrestten kaynaklanan ölümlerin bireylerin yaşadıkları yerlerde ve gündüz saatlerinde (08-18:00) meydana geldiği belirlenmiştir (2,7). Literatürde YouTube sayfalarında bulunan kardiyopulmoner resusitasyon uygulama videolarını ve bu videoların Amerikan Kalp Derneği'nin (American Heart Association -AHA) 2015 yılında yayınladığı güncel kılavuzlara uygunluğunu değerlendiren sınırlı sayıda araştırma bulunmaktadır (8)(9)(10). Bu çalışmanın amacı, Türkçe YouTube sayfalarında yer alan yetişkin CPR videolarının 2015 CPR kılavuzuna uygunluğunu değerlendirmektir.…”
unclassified